"Burnt by the scorching sun": climate-induced livelihood transformations, reproductive health, and fertility trajectories in drought-affected communities of Zambia - Joseph G. Rosen; Drosin Mulenga; Lyson Phiri; Natasha Okpara; Caila Brander; Nachela Chelwa; Michael T. Mbizvo (BMC, 2021)
Abstract Background Climate-induced disruptions like drought can destabilize household and community livelihoods, particularly in low- and middle-income countries. This qualitative study explores the impact of severe and prolonged droughts on gendered livelihood transitions, women's social and financial wellbeing, and sexual and reproductive health (SRH) outcomes in two Zambian provinces. Methods In September 2020, in-depth interviews (n = 20) and focus group discussions (n = 16) with 165 adult women and men in five drought-affected districts, as well as key informant interviews (n = 16) with civic leaders and healthcare providers, were conducted. A team-based thematic analysis approach, guided by the Framework Method, was used to code transcript text segments, facilitating identification and interpretation of salient thematic patterns. Results Across districts, participants emphasized the toll drought had taken on their livelihoods and communities, leaving farming households with reduced income and food, with many turning to alternative income sources. Female-headed households were perceived as particularly vulnerable to drought, as women's breadwinning and caregiving responsibilities increased, especially in households where women's partners out-migrated in search of employment prospects. As household incomes declined, women and girls' vulnerabilities increased: young children increasingly entered the workforce, and young girls were married when families could not afford school fees and struggled to support them financially. With less income due to drought, many participants could not afford travel to health facilities or would resort to purchasing health commodities, including family planning, from private retail pharmacies when unavailable from government facilities. Most participants described changes in fertility intentions motivated by drought: women, in particular, expressed desires for smaller families, fearing drought would constrain their capacity to support larger families. While participants cited some ongoing activities in their communities to support climate change adaptation, most acknowledged current interventions were insufficient. Conclusions Drought highlighted persistent and unaddressed vulnerabilities in women, increasing demand for health services while shrinking household resources to access those services. Policy solutions are proposed to mitigate drought-induced challenges meaningfully and sustainably, and foster climate resilience.